2018
DOI: 10.7759/cureus.2150
|View full text |Cite
|
Sign up to set email alerts
|

“Lazarus Response” to Olaparib in a Virtually Chemonaive Breast Cancer Patient Carrying Gross BRCA2 Gene Deletion

Abstract: This report describes an estrogen receptor-positive breast cancer patient, who relapsed at two and a half years after the completion of adjuvant chemotherapy while being on the aromatase inhibition. Based on the clinical evidence for potential sensitivity of the tumor to hormone ablation, everolimus was added to continuing exemestane treatment. Oral chemotherapy was administered at further disease progression, however, it lasted only for 10 days due to rapidly deteriorating condition of the patient. BRCA test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…The analysis of tumors exposed to platinum therapy or PARPi revealed instances of the rescue of BRCA1/2 function, which is achieved by the second mutation in the affected gene, and, consequently, by the restoration of BRCA1/2 open reading frame [ 24 , 28 ]. These data are supported by clinical observations of extraordinarily good response in patients with deletion of large fragments of BRCA1/2 genes, i.e., in instances where BRCA1/2 function cannot be restored by the secondary mutation [ 51 , 77 ]. Studies on BRCA1 -mutated ovarian carcinomas demonstrated the persistence of a small fraction of BRCA1-proficient cells even in chemonaive tumors; these cells rapidly repopulate tumor mass during the first weeks of platinum-based therapy thus explaining the phenomenon of inevitable emergence of platinum-resistance [ 78 , 79 ].…”
Section: Acquired Resistance To Brca1/2 -Specifc Therapysupporting
confidence: 54%
“…The analysis of tumors exposed to platinum therapy or PARPi revealed instances of the rescue of BRCA1/2 function, which is achieved by the second mutation in the affected gene, and, consequently, by the restoration of BRCA1/2 open reading frame [ 24 , 28 ]. These data are supported by clinical observations of extraordinarily good response in patients with deletion of large fragments of BRCA1/2 genes, i.e., in instances where BRCA1/2 function cannot be restored by the secondary mutation [ 51 , 77 ]. Studies on BRCA1 -mutated ovarian carcinomas demonstrated the persistence of a small fraction of BRCA1-proficient cells even in chemonaive tumors; these cells rapidly repopulate tumor mass during the first weeks of platinum-based therapy thus explaining the phenomenon of inevitable emergence of platinum-resistance [ 78 , 79 ].…”
Section: Acquired Resistance To Brca1/2 -Specifc Therapysupporting
confidence: 54%
“…18,24,25 A single case report describes a patient with estrogen receptor-positive metastatic breast cancer and a large BRCA2 gene deletion who had a complete response to olaparib. 26 In patients with advanced OC and germline BRCA mutations who have received at least 2 lines of previous chemotherapy, olaparib maintenance has been shown to prolong PFS compared with placebo (median, 19.1 vs 5.5 months; hazard ratio [HR], 0.30; 95% CI, 0.22-0.41). 27 Another study of maintenance olaparib in a similar population showed a trend toward improved OS in women on olaparib versus placebo (HR, 0.73; 95% CI, 0.45-1.17) and a median OS of 34.9 months in women with germline BRCA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1/2 LGRs are not specifically considered in the studies on tumor drug sensitivity. However, there are case reports supporting exceptional responsiveness of BRCA1/2 LGR-associated tumors to PARPi[ 33 ].…”
Section: Restoration Of Brca1/2 Function By Secondary Somatic Mutationsmentioning
confidence: 99%